Effect of Use of Substituted Oil Palm Shell Boiler Ash on Cement and Substituted Glass Powder on Fine Aggregate on Concrete Compressive Strength - Syafwandi, Syafwandi; Fatoni, Adrian (Journal of World Conference (JWC), 2020)
This research aims to determine the effect of palm shell boiler ash substituted in cement and glass powder substituted on fine aggregate in concrete mixes on compressive strength and slump values and to determine the usefulness of the concrete. This research used an experimental method with 9 variations of substitution materials, a total of 60 samples of cube-shaped test specimens measuring 15cmx15cmx15cm. The variation of Oil palm shell boiler substitution used is 0%, 6%, 8%, and 10%, and for glass powder substitution variation is 0%, 5%, 10%, and 15%. From the results of the compressive strength test conducted on the 7th day, the substitution of 8% Oil palm shell boiler Ash and 10% glass powder or variation E received the highest compressive strength result of 19,593 MPaWhile on the 28th day, substitution of 6% oil palm shell boiler ash and 5% glass powder or variation A received the highest compressive strength yield of 22,630 MPa.